How fitting is "one-size-fits-all"? Revisiting the dynamic effects of ECB's interest policy on euro area countries - Maybrit Wächter; Christian Proano; Juan Carlos Pe\~na (Bamberg University, Bamberg Economic Research Group (BERG), 2024)
This paper revisits the "one-size-fits-all" challenge posed by the European Central Bank's (ECB) monetary policy within the heterogeneous economic landscape of the euro area. Using a dataset spanning from 1999Q1 to 2019Q4 for the ECB interest rate and from 2004Q4 onwards for the Wu-Xia shadow rate, we compute country-specific hypothetical Taylor rates across EU-11 countries and examine the dynamic effects of the difference between these rates and the actual ECB policy rate, the so-called Taylor Rate Gaps (TRGAPs), on GDP growth and inflation. Employing panel and country-specific local projections, our findings reveal that positive TRGAPs negatively impact economic growth, with this effect being more pronounced in periphery countries compared to core countries. The analysis highlights the limitations of a uniform monetary policy in addressing the diverse economic conditions within the euro area, suggesting the need for a more tailored approach to foster balanced and sustainable growth across the region.
Keywords: 330; Monetary Policy; Taylor Rule; Euro Area; Economic Growth; Interest Rate Gap